Упростите выражение: 1) −1,6x · (−5y); 3) a − (a − 8) + (12 + a); 2) −7a − 9b + a +...

0 голосов
103 просмотров

Упростите выражение: 1) −1,6x · (−5y); 3) a − (a − 8) + (12 + a); 2) −7a − 9b + a + 11b; 4) −3(c − 5) + 6(c + 3).


Математика (28 баллов) | 103 просмотров
Дан 1 ответ
0 голосов

Ответ:

Пошаговое объяснение:

1) −1,6x · (−5y) = 8xy

3) a − (a − 8) + (12 + a) = a - a + 8 + 12 + a = a + 20

2) −7a − 9b + a + 11b = -6a + 2b

4) −3(c − 5) + 6(c + 3) = -3c + 15 + 6c + 18 = 3c + 33

(187k баллов)